Konsep Dasar Manajemen Sumber Daya Manusia Dalam Perspektif Pendidikan Islam - Marsona, Khadijah; Hamdi Abdul Karim (Journal of Practice Learning and Educational Development, 2025)
Human Resource Management (HRDM) in Islamic education plays a strategic role in shaping professional and educational educators with noble character. This article aims to examine the basic concepts of HRDM from the perspective of Islamic education, emphasizing the importance of integrating spiritual, moral, and professional values in the management of human resources in Islamic educational institutions. This research utilizes the library research method, analyzing various relevant literature, journals, and research findings. The study results indicate that HRDM in Islamic education is not only focused on efficiency and productivity, but also on applying Islamic principles such as trust, justice, responsibility, and cooperation in every managerial aspect. The main functions of HRDM in Islamic education include planning, organizing, directing, supervising, and developing individual potential based on Islamic values. The ultimate goal is to create human resources who are competent, possess good morals, and are able to make a positive contribution to the progress of educational institutions and the benefit of the people. Thus, the basic concept of HRDM from an Islamic perspective becomes an important foundation for realizing an education system that is holistic, equitable, and oriented toward Divine values.